Direct emission of methane and nitrous oxide from switchgrass and corn stover: implications for large‐scale biomass storage. Issue 4 (3rd June 2014) - Emery, Isaac; Mosier, Nathan
Abstract Little is known about the contributions of biomass feedstock storage to the net greenhouse gas emissions from cellulosic biofuels. Direct emissions of methane and nitrous oxide during decomposition in storage may contribute substantially to the global warming potential of biofuels. In this study, laboratory‐scale bales of switchgrass and corn stover were stored under a range of moisture (13.0–32.9%) and temperature (5–35 °C) conditions and monitored for O2 consumption and CO2, CH4, and N2O production over 8 weeks. Gas concentrations and emissions rates were highly variable within and between experimental groups. Stover bales produced higher CO2 concentrations (P = 0.0002) and lower O2 (P < 0.0001) during storage than switchgrass bales. Methane concentrations (1.8–2100 ppm) were inversely correlated with bale moisture (P < 0.05), with emissions rates ranging from 4.4–914.9 μg kg−1 DM day−1. Nitrous oxide concentrations ranged from 0 to 31 ppm, and emissions from switchgrass bales inversely correlated with temperature and moisture (P < 0.0001). Net global warming potential from each treatment (0–2.4 gCO2e kg−1 DM) suggests that direct emission of methane and nitrous oxide from aerobically stored feedstocks have a small effect on net global warming potential of cellulosic biofuels.